(untitled) (Global Scientific Review, 2023)
In this article, the concept of an administrative act, the role and importance of an administrative act in legislation and practice of Uzbekistan, the specific characteristics of an administrative act, as well as the significance of the correct analysis of an administrative act were analyzed. At the same time, the problems arising in practice in understanding administrative acts and its application were studied.